Comparison of Hajj Fund Investment Policies Between Indonesia and Malaysia: Analysis Study of Management, Governance, and Global Challenges - Adzkia, Afaf Fadhila; Aspandi, Aspandi; Lamor, Assama (TSARWAH, 2024)
The Hajj pilgrimage has a high spiritual value and is obligatory for Muslims who are physically and financially able. The implementation of the Hajj pilgrimage requires significant costs, both for departure and services in the holy land, so the management of Hajj funds is a crucial aspect to ensure the sustainability and efficiency of services. In Indonesia, Hajj funds are managed by the Hajj Financial Management Agency (BPKH), which uses sharia-based investment instruments to optimize investment returns and support the financing of the Hajj pilgrimage. In contrast, Malaysia through the Hajj Savings Institution (TH) manages Hajj funds with a more integrated approach, which includes not only investment, but also savings and subsidies for Hajj pilgrims. The management and investment of Hajj funds in Indonesia focus on investment diversification in sharia capital market instruments, while Malaysia emphasizes real asset-based management such as property and agribusiness. These differences reflect differences in the economic context, regulations, and institutional capacity of each country. Good governance plays an important role in building public trust in the management of Hajj funds. This study aims to examine the differences in hajj fund management and investment policies between Indonesia and Malaysia, the role of good governance in building public trust, and the opportunities and challenges in aligning the hajj fund investment policies of the two countries to face global challenges. The method used in this study is a literature study. The results of the study are expected to contribute to the development of transparent, accountable, and sharia-compliant hajj fund investment policies.